Beyond Univariate Measurement of Spatial Autocorrelation : Disaggregated Spillover Effects for Indonesia - Day, Jennifer (Taylor and Francis, 2013)
Most studies that incorporate spatial effects use a very limited number of spatial variables in the growth model, e.g. growth spillovers or infrastructure impacts of neighbouring regions. This article innovates on previous work in spatial econometrics by differentiating among spatial contributions to economic development; e.g. infrastructure, capital, human capital, land and labour. We explore whether including more spatial effects can improve the viability of a growth model, and also test the hypothesis that the differential spatial effects of various important predictor variables are discernible for Indonesia.